Influence of No-Tillage on Soil Organic Carbon, Total Soil Nitrogen, and Winter Wheat (Triticum aestivum L.) Grain Yield - Peter Omara; Lawrence Aula; Elizabeth M. Eickhoff; Jagmandeep S. Dhillon; Tyler Lynch; Gwendolyn B. Wehmeyer; William Raun (International Journal of Agronomy)
No-tillage (NT) can improve soil properties and crop yield. However, there are contrasting reports on its benefits compared to conventional tillage (CT). Dataset (2003–2018) from long-term continuous winter wheat (Triticum aestivum L.) experiments 222 (E222) at Stillwater and 502 (E502) at Lahoma in Oklahoma, USA, established in 1969 and 1970, respectively, was used. Both experiments were managed under CT until 2010 and changed to NT in 2011. In each tillage system, treatments included nitrogen (N) rates at E222 (0, 45, 90, and 135 kg·N·ha−1) and E502 (0, 22.5, 45, 67, 90, and 112 kg·N·ha−1). The objective was to determine the change in wheat grain yield, soil organic carbon (SOC), and total soil nitrogen (TSN) associated with the change to NT. Grain yield was recorded, and postharvest soil samples taken from 0–15 cm were analyzed for TSN and SOC. Average TSN and SOC under NT were significantly above those under CT at both locations while grain yield differences were inconsistent. Under both tillage systems, grain yield, TSN, and SOC increased with N rates. At E222, grain yield, TSN, and SOC under NT were 23%, 17%, and 29%, respectively, more than recorded under CT. At E502, grain yield was lower under NT than CT by 14% while TSN and SOC were higher by 11% and 13%, respectively. Averaged over experimental locations, wheat grain yield, TSN, and SOC were 5%, 14%, and 21%, respectively, higher under NT compared to CT. Therefore, NT positively influenced grain yield, TSN, and SOC and is likely a sustainable long-term strategy for improving soil quality and crop productivity in a continuous monocropping system.